Nascent Desires: Gendered Sexualities in Life Orientation Sexuality Education Programmes and Popular Music - Moodley, Dale Dhersen (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
Formal school-based sexuality education is one medium, amongst others, that recognises young people's sexuality, but usually as at-risk and/or risk taking subjects, or as innocent subjects. I analyse the gendered sexualities of young people as represented in: Grade 10 Life Orientation sexuality education programmes and popular music, as two mediums of sexual socialisation in Grade 10 learners' lives, and as engaged with by Grade 10 learners and educators. I collected data from two schools in the Eastern Cape that included: (i) sections on sexuality from two Life Orientation manuals used by educators in classrooms: 'Oxford Successful Life Orientation' (2011), and 'Shuters Top Class Life Orientation' (2011); (ii) videos and lyrics of three songs voted most popular by learners which were 'Climax' by Usher, 'Beez in the Trap' by Nicki Minaj, and 'Where Have You Been' by Rihanna; (iii) observations of seven sexuality education classes; and, (iv) in-depth semistructured interviews conducted with eight learners and two educators. I draw on an integrated theoretical and methodological approach "“ Foucauldian, feminist poststructural and psychosocial psychoanalytic perspectives "“ to conceptualise and analyse gendered sexualities in terms of: (i) the dominant gendered discourses found in sexuality education manuals, and music videos and lyrics; (ii) the reflexive and interactive gendered subject positions taken up and/or resisted by learners and educators during classroom lessons and one-on-one interviews; and, (iii) learners' and educators' conscious and unconscious investments in particular gendered subject positions during one-on-one interviews. These three sets of analysis produced four major themes. The first theme centres on responsible sexuality; young women are expected to assume more sexual responsility than young men, thus curbing their sexual agency. The second theme outlines three types of pleasure "“ sexual, romantic and dating and/or relationship pleasure "“ that accord young men and women active and passive ways of exercising pleasure. The third theme highlights the heteronormative transitioning adolescent subject that constructs young women as reproductive subjects and young men as sexual subjects. The last theme focuses on gendered power relations and raunch culture, and maintains that young men are powerful and likely to commit acts of sexual violence against young women because they are powerless. The central argument developed when viewing all the themes is that dominant gendered discourse, gendered subject positions, and conscious and unconscious investments in these positions challenge the extent to which the gendered meanings that underpin adolescent learners' sexuality are stable and fixed. The gendered discourses in the Life Orientation sexuality education programmes showed that gender is expressed rigidly, thus privileging masculine over feminine sexuality. However, the gendered discourses in the popular music contested rigid gender binaries and produced fluid and equitable masculine and feminine sexualities. The classroom practices depicted multiple and more equatable gendered sexualities, highlighting just how contested gender is. Finally, educator and learners' personal biographies illustrated how conflicting masculine and feminine sexualities present a signficant source of emotional conflict for them. It may benefit policymakers and stakeholders to consider informal mediums of sexual socialisation for learners, such as music, when drafting the Life Orientation sexuality education curriculum, whilst also taking into account learners and educators personal lives.
Keywords: Uncatalogued